2019
DOI: 10.1021/acssuschemeng.9b06716
|View full text |Cite
|
Sign up to set email alerts
|

Lignin Nanoparticles: Green Synthesis in a γ-Valerolactone/Water Binary Solvent and Application to Enhance Antimicrobial Activity of Essential Oils

Abstract: Lignin nanoparticles (LNPs), as a special aggregate of renewable and biodegradable lignin available in abundant amounts, are a perfect building-block material because of their advantages, including good dispersibility in water, great biocompatibility, and eco-friendly characteristics. To exploit a promising method of producing LNPs, we developed a simple and sustainable synthesis approach using a recycled γ-valerolactone (GVL)/water binary solvent (GWBS). Up to 200 g/L lignin from several sources could be comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 47 publications
1
49
0
Order By: Relevance
“…With The development of material science, The regular structure of nanomaterials is essential to The design of functional materials for advanced applications. Moreover, The recent progress in The preparation of lignin nanoparticles (LNPs) inspired The design of lignin-based functional materials [16][17][18]. Thus, The green synthesis of well-dispersed Au NPs with LNPs is important for The preparation of composite lignin-derived materials.…”
Section: Introductionmentioning
confidence: 99%
“…With The development of material science, The regular structure of nanomaterials is essential to The design of functional materials for advanced applications. Moreover, The recent progress in The preparation of lignin nanoparticles (LNPs) inspired The design of lignin-based functional materials [16][17][18]. Thus, The green synthesis of well-dispersed Au NPs with LNPs is important for The preparation of composite lignin-derived materials.…”
Section: Introductionmentioning
confidence: 99%
“…Though the concentration of lignin used, 3–9 wt %, in our research is much higher than the reported 0.05–2% [ 28 , 29 , 30 ] in the THF system, the obtained LNPs display uniform particle size. This will certainly solve one of the major issues of industrial lignin that hinges on low dissolution rates in ordinary organic solvents with meager yields [ 9 , 26 ], which could be a significant breakthrough but warrants further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent to the dripping of the lignin–DES solution into water, some highly hydrophobic lignin molecules could form a membrane at the two-phase interface between water and DES, causing water to be entrapped, and forming a balance between the continuous phase and the dispersed phase [ 9 ]. The lignin–DES solution will then be wrapped with the membrane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Applications of lignin nanoparticles in UV protection [ 121 ], antibacterial [ 122 ], mineral flotation [ 123 ], pickering emulsions [ 108 ], cosmetics [ 109 ], anticorrosion [ 124 ] and drug carriers have also been reported in the literature [ 112 ]. Wang et al prepared lignin nanoparticles via solvent exchange combined with the ultrasound process, and the UV adsorbing ability of these lignin nanoparticles was subsequently tested [ 109 ].…”
Section: Preparation Of Lignin Nanoparticles and Their Applicationmentioning
confidence: 99%